(untitled) (Asian Journal of Ethnobiology, 2024)
Abstract. Ayuningrum LS, Setyaningrum M, Agustin MR, Sabrina MA, Arifiani KN, Nazar IA, Md Naim D, Setyawan AD. 2024. Ethnobotanical study of homegarden by local communities in the urban area of Surakarta City, Central Java, Indonesia. Asian J Ethnobiol 7: 79-88. Communities in Surakarta City, Central Java Province, Indonesia, utilize many plants from their homegardens daily. Urban homegardens have the potential to provide biological, social, and economic environmental services. However, documentation and further information on local knowledge of food crops and plant diversity in homegardens is still limited and needs to be presented. This study aims to document and reveal local knowledge of the diversity of homegarden plants for daily life in Mojosongo, Kestalan, and Nusukan Villages, Surakarta City, and homegarden patterns in these villages. Data collection was conducted in December 2023 through surveys and direct interviews using the simple random sampling method, with 72 respondents interviewed, with details of 6 men and 66 women. The majority of respondents have a high school/equivalent educational background. The age range of respondents was dominated by 56-65 years. Plant inventory amounted to 148 species from 55 families, consisting of 73 species of food plants, 19 species of medicinal plants, 18 species of shade, 66 species of ornamental plants, and 2 species of mystical plants. The most common growth form found is the type of tree (54 species), and the family found is Zingiberaceae (11 species), followed by Araceae (8 species) and Solanaceae (7 species). Therefore, the study’s results show that homegarden plants used by the community are divided into five categories of use: food, medicine, shading, ornamental, and mystical. Local people use many food plants daily, and a homegarden can be an alternative source of diverse and nutritious food plants for households.